Better with your parasites? Lessons for behavioural ecology from evolved dependence and conditionally helpful parasites. (August 2016) - Weinersmith, Kelly L.; Earley, Ryan L.
Abstract : Interest in how parasites shape host behaviour has increased dramatically in recent years. The main focus of behavioural ecologists has been on the negative effects of parasites on host behaviour. However, there are instances in which infected hosts express more adaptive behavioural phenotypes and have higher fitness relative to uninfected hosts, suggesting that it is sometimes beneficial to be parasitized. For example, hosts can exhibit evolved dependence, wherein the host coevolves with and comes to depend on parasites for the expression of adaptive host behaviours. Additionally, 'conditionally helpful parasites' modify the host phenotype in ways that benefit the host under particular conditions. These scenarios have been explored in the context of bacterial or fungal symbionts, but have been relatively unstudied with regard to metazoan parasites (e.g. trematodes, acanthocephalans, nematodes and cestodes). We explore how these scenarios apply to hosts infected by metazoan parasites, and consider implications for research in behavioural ecology. We examine conditions under which infection should result in more adaptive host behavioural phenotypes, and the implications for host fitness and evolution. We then discuss the implications of conditionally helpful parasites and parasites for which hosts have evolved dependence for laboratory studies of host behaviour and for conservation and reintroduction programmes. Highlights: Hosts may express more adaptive behavioural phenotypes when infected by parasites. Evolved dependence can result in detrimental host behaviour when parasites are lost. Conditionally helpful parasites can modify host behaviour and benefit the host. These phenomena have implications for lab studies of behaviour, and conservation. Parasites should be included in ecologically relevant studies of host behaviour.